International water resources allocation and conflicts - the case of the Euphrates and the Tigris - Mehmet Kucukmehmetoglu; Jean-Michel Guldmann (European Regional Science Association (ERSA), 2002)
The Mesopotamia region, within the boundaries of Turkey, Iraq, and Syria, is populated by different ethnic, national, and religious groups (Turks, Arabs, Kurds, Sunnis and Shiites), which have long fought over the control of its fertile lands. Since the early 1970's, there has been an increase in tension among these three countries, primarily related to the sharing of the waters of the Euphrates and Tigris rivers. In particular, Turkey's development of Southeastern Anatolia, with water needed for agricultural and energy production projects, has been viewed as a threat to the well-being of Syria and Iraq. This water problem is likely to be exacerbated in the future, when water demand grows in both quantity and quality due to high population growth and urban development. This paper presents a water allocation optimization model, that represents, in network form, the system made of the two rivers and their various consumption (agriculture, urban centers, hydropower plants) and transshipment nodes, including the possibility of transferring water from the Euphrates to the Tigris. The basic model maximizes the aggregate net benefits of the three countries, including the gross benefits from water uses in agriculture, urban functions, and hydroelectricity, minus the costs of water conveyance. The model is formulated as a linear program, and accounts for both evaporation and return flows from consumptive uses. In view of the uncertainty surrounding the values of several parameters (e.g., agricultural benefit derived from using a gallon of water), the model is first used to carry systematic sensitivity analyses to identify the critical parameters. Next, the model is used to generate the net benefit Pareto surface, using multi-objective programming techniques. The systematic analysis of this surface provide information about the benefit trade-offs between any two countries. Finally, cooperative game theory concepts (core, Shapley value, nucleolus) are used to identify stable water allocations, where all three countries find it beneficial to cooperate. These various analyses are carried out under different scenarios related to future energy prices, agricultural production efficiency, and total water availability. The policy implications of the results are discussed, and areas for further research are outlined.
Keywords: 330